Chapter Personal weaknesses recognized by high school students in the North-West of Italy - BOLLANI, Luigi (Proceedings e report, 2021)
This study is part of a project aimed at supporting the weaknesses of young people who are experiencing, or are at risk of reaching, NEET condition (Not in Education, Employment or Training; aged between 15 and 29 or 34, according to different definitions). The first signs of the extreme discomfort caused by Neet condition were sought by investigating signs of weakness in high school students in the Piedmont, Valle d'Aosta and Liguria regions. Of course students as such are not Neets and the anonymity required for a survey dealing with very personal issues does not allow a longitudinal study to be carried out on the same individuals. However, the construction of a comparison base referring to a generic population, relative to the incidence of certain states of weakness (or some of their combinations), will allow for a subsequent comparison with the incidence of the same difficulties in school age for those who find themselves in a Neet situation. A survey questionnaire was administered to 931 students, an operator being present in the classrooms, shortly before the start of the pandemic. Collected results will therefore be more directly linked to school activities "in presence", even if discontinuities in teaching methods and characteristics caused by the pandemic might have brought in alterations that will need to be monitored over time.